Polymeric liquids in mesoporous photonic structures: From precursor film spreading to imbibition dynamics at the nanoscale - Dittrich, Guido (2024)
Polymers are known to wet nanopores with high surface energy through an atomically thin precursor film followed by slower capillary filling. We present here light interference spectroscopy using a mesoporous membrane-based chip that allows us to observe the dynamics of these phenomena in situ down to the sub-nanometer scale at milli- to microsecond temporal resolution. The device consists of a mesoporous silicon film (average pore size 6 nm) with an integrated photonic crystal, which permits to simultaneously measure the phase shift of thin film interference and the resonance of the photonic crystal upon imbibition. For a styrene dimer, we find a flat fluid front without a precursor film, while the pentamer forms an expanding molecular thin film moving in front of the menisci of the capillary filling. These different behaviors are attributed to a significantly faster pore-surface diffusion compared to the imbibition dynamics for the pentamer and vice versa for the dimer. In addition, both oligomers exhibit anomalously slow imbibition dynamics, which could be explained by apparent viscosities of six and eleven times the bulk value, respectively. However, a more consistent description of the dynamics is achieved by a constriction model that emphasizes the increasing importance of local undulations in the pore radius with the molecular size and includes a sub-nanometer hydrodynamic dead, immobile zone at the pore wall but otherwise uses bulk fluid parameters. Overall, our study illustrates that interferometric, opto-fluidic experiments with mesoporous media allow for a remarkably detailed exploration of the nano-rheology of polymeric liquids.